Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Ask your questions and receive precise answers from experienced professionals across different disciplines. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

Solve for \( x \).

[tex]\[ \frac{1}{5}x - 4 = 3(x - 5) \][/tex]


Sagot :

Let's solve the equation step-by-step:

Given the equation:
[tex]\[ \frac{1}{5} x - 4 = 3(x - 5) \][/tex]

1. Distribute the 3 on the right-hand side:
[tex]\[ \frac{1}{5} x - 4 = 3x - 15 \][/tex]

2. Isolate the \( x \) terms on one side and the constants on the other side:
[tex]\[ \frac{1}{5} x - 3x = -15 + 4 \][/tex]

3. Combine the constants on the right-hand side:
[tex]\[ \frac{1}{5} x - 3x = -11 \][/tex]

4. To combine the \( x \) terms, we need to express \(\frac{1}{5} x\) in a form that can be easily combined with \(3x\):
[tex]\[ \frac{1}{5} x = \frac{x}{5} \][/tex]
So we rewrite the equation:
[tex]\[ \frac{x}{5} - 3x = -11 \][/tex]

5. Clear the fraction by multiplying every term by 5:
[tex]\[ x - 15x = -55 \][/tex]

6. Combine like terms:
[tex]\[ -14x = -55 \][/tex]

7. Solve for \( x \) by dividing both sides by -14:
[tex]\[ x = \frac{-55}{-14} \][/tex]
[tex]\[ x = \frac{55}{14} \][/tex]

So the solution to the equation is:
[tex]\[ x = \frac{55}{14} \approx 3.9285714285714284 \][/tex]